Cyberfield: Theory, Methodology, and Practice - Svetlana Yu. Belorussova; Ksenya A. Maretina; Elizaveta A. Komova (Changing Societies & Personalities, 2025)
The study of digital identity began in the late 1980s with the rise of computers, the Internet, video games, and online communication tools. Over the past 35 years, digital anthropology and ethnography have provided valuable insights into virtual interactions. However, due to rapid technological advancements, researchers must continually update their methodologies to stay aligned with new trends in online communication. This study seeks to explore and systematize theories, methodologies, and practices related to the cyberfield, offering a comprehensive understanding of current research in digital ethnography. Additionally, it introduces an alternative methodology for analyzing the cyberfield, emphasizing its advantages in capturing the complexities of online spaces. The methodological principles outlined in this article are illustrated through examples from the authors’ own study of the ethnic identity of minor Indigenous peoples in Russia in the online environment. Today, virtual spaces offer various research opportunities, including qualitative and quantitative methods, surveys, and database creation, enhancing data collection. Web analysis has simplified fieldwork by reducing the need for physical presence, saving time and resources. However, recent developments suggest that real-world interaction remains crucial. The growing intersection of the “digital” and “physical” fields highlights the importance of integrating both contexts in ethnographic research for a more nuanced understanding of virtual and real-world experiences.